STUDENTS’ POST-CLASS ACTIVITY AND LEARNING ACHIEVEMENT USING COOPERATIVE MODEL OF STUDENT TEAMS ACHIEVEMENT DIVISIONS ON OSCILLATION AND WAVE TOPIC - Roudhoutul Aulia Rochim; Nur Kuswanti; Noer Af'idah (Jurnal Pembelajaran Sains, 2020)
Science learning was still dominated by the lecture model. Consequently, students were less active and difficult in the learning process. The difficulty was caused by the low teacher ability to manage it so that the learning was less effective and interesting. As a result student’s interest and learning achievement in learning science was low. Therefore, a learning model is needed to support student mastery. One of them was the cooperative learning model of student teams achievement divisions. This research aimed to describe the activities and student learning outcomesafter learning using a cooperative learning model of student teams achievement divisions on Vibration and Wave. This study was a descriptive research with a quantitative approach. It used One-Shot Case Study. The Subjects of this study were students of class VIII of State Junior High School 3 Jombang consisting of 30 students. Student activities were observed by the student activities sheet. Learning outcomes were determined based on mastery of students and mastery of learning indicators on minimal mastery criteria. The results of the research showed that: (1) Studentactivities at the first and second meetings reached 89,5% with very good criteria, (2) Student learning outcome reached 77% while the learning indicator value got 86,5 with mastery category.